2019
DOI: 10.1097/gox.0000000000002187
|View full text |Cite
|
Sign up to set email alerts
|

To Glue or Not to Glue? Analysis of Fibrin Glue for Split-thickness Skin Graft Fixation

Abstract: Background: Split-thickness skin grafting (STSG) is a commonly used tool in the plastic surgeon’s reconstructive armamentarium. Fibrin glue (FG) consists of a combination of clotting factors and thrombin whose key properties include adherence and hemostasis. This preliminary study aimed to assess clinical outcomes and cost of FG for STSG fixation in a general wound reconstruction. Methods: A retrospective review was conducted in all patients undergoing STSG placement by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Physicians from a center in Nottingham applied fibrin for removal of hair cyst from the sacrococcygeal region (pilonidal cyst). After two rounds of curettage, the method was found 97% effective [9,26,[30][31][32][33][34][35][36].…”
Section: Aesthetic Medicinementioning
confidence: 99%
“…Physicians from a center in Nottingham applied fibrin for removal of hair cyst from the sacrococcygeal region (pilonidal cyst). After two rounds of curettage, the method was found 97% effective [9,26,[30][31][32][33][34][35][36].…”
Section: Aesthetic Medicinementioning
confidence: 99%
“…Existing biomaterials studied for grafts' or devices' adhesives or glues [22][23][24][25][26][27][28][29][30] covered proteins such as fibrin, 25 gelatin, 31,32 and albumin, 33 polysaccharides 34,35 such as dextran and chitosan and synthetic polymers such as poly (ethylene glycol) (PEG) and [36][37][38] polyurethanes (PU), 39 which are biocompatible with sufficient mechanical strength. Moreover, adhesives should be capable of adhering to surrounding tissues by chemical bonds, interpenetration or physical linkage such as hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Biologic fibrin glues have been applied to support skin graft survival since World War II [10,11]. Since early reports, multiple studies have shown that fibrin glues can reduce operative times, hematoma risk, need for negativepressure wound therapy and bolsters, with equivalent graft survival rates [12][13][14][15]. Herein, we describe the successful use of biologic fibrin glue with split-thickness skin graft reconstruction of a cutaneous facial defect.…”
Section: Introductionmentioning
confidence: 99%